2019
DOI: 10.1139/apnm-2018-0311
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance dynamics during short-term high-intensity functional training

Abstract: CrossFitTM (CF) is a form of high-intensity functional training (HIFT) that focuses on training across the entire spectrum of physical fitness. CF has been shown to improve a number of indicators of health but little information assessing energy balance exists. The purpose of the present study was to investigate energy balance during 1 week of CF training. Men and women (n = 21, mean age and BMI: 43.5 ± 8.4 y; 27.8 ± 4.9 kg·m-2), with ≥ 3 months CF experience, had body composition assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…of the studies reviewed, 7 (7%) utilized online documents (i.e. online databases, medical records) and 1 study [122] used interviews to examine the factors that promoted participation in crossFit training among pregnant women. because of the nature of crossFit training, it makes sense that experimental designs are most common.…”
Section: Methodsmentioning
confidence: 99%
“…of the studies reviewed, 7 (7%) utilized online documents (i.e. online databases, medical records) and 1 study [122] used interviews to examine the factors that promoted participation in crossFit training among pregnant women. because of the nature of crossFit training, it makes sense that experimental designs are most common.…”
Section: Methodsmentioning
confidence: 99%
“…Observational studies have demonstrated that CrossFit athletes’ dietary intake is frequently below recommendations [ 13 ]. Maintaining a deficit in energy intake could be a valuable strategy to target weight loss reduction in overweight or obese individuals [ 1 ]. On the other hand, switching energetic metabolism (from carbohydrate to fat recruitment) could be beneficial for athletes.…”
Section: Discussionmentioning
confidence: 99%
“…CrossFit is a well-known, widely spread, new type of exercise training consisting of high-intensity and endurance activities, while presenting functional exercises as a major component. Thanks to CrossFit characteristics, athletes can simultaneously improve strength and aerobic performances and decrease body fat efficiently [ 1 , 2 ]. This type of training, usually composed of high-intensity exercise involving upper and lower body exercise with a short rest, especially when associated with uncontrolled progressive overload, may result in fatigue exacerbated by a non-suitable recovery that could subsequently lead to a higher risk of musculoskeletal injuries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of force analysis, we have made clear that among the several external forces to which the human body is subjected, static friction does not do work, so it does not bring about energy conversion. In the whole process, we only need to consider the work of two forces, namely the work of the arm and the force of gravity [18][19]. In the rising process, the upward pulling force is the same as the displacement direction, so it does positive work, and the vertical downward gravity is opposite to the displacement direction, so it does negative work.…”
Section: People Practice Pullupsmentioning
confidence: 99%